Clarifying high performance and the role, responsibilities, and requisite attributes of the high-performance director in American professional sport - DeWeese, B. H.; Hamilton, D. K.; Huls, S.; Peterson, B. J.; Rath, T.; Althoff, A. (Strength and Conditioning Journal, 2023)
North American professional sport continues to evolve by adopting robust performance development strategies that place a premium on player care and competitive readiness. These strategies can be demonstrated by the increase of clubs implementing high-performance departments to maximize service quality rendered to rostered players. Although this transition to an integrated approach to player care is appreciated, it has become evident that there is a need to clarify the role, responsibilities, and job demands of high-performance directors. This emerging executive position is charged with leading complex systems of intertwined departments through the development of an environment that fosters a transdisciplinary approach to athlete preparation and care through enhanced organizational communication and the reduction of disciplinary silos that can thwart collaboration. Therefore, the current article describes the high-performance environment, allowing for a more accurate definition and representation of a modern high-performance director. The current article relies on the authors' collective experience as current professional-sport high-performance leaders to provide meaningful recommendations and insight into the field.